Changes in anemia prevalence and the proportion of anemia associated with iron deficiency or inflammation in young children residing in Puno, Peru: Analysis using new World Health Organization guidelines for defining anemia - Cinthya Vásquez-Velásquez; Benita Maritza Choque-Quispe; Parminder S. Suchdev; Chris A. Rees; Vilma Tapia; Yi-An Ko; Gustavo F. Gonzales (PLoS ONE, 2026)
Background In 2024, the World Health Organization (WHO) introduced new hemoglobin cutoffs for diagnosing anemia. The WHO also incorporated revised altitude adjustments and lowered thresholds to diagnose anemia for children aged 6–23 months. Puno, Peru has historically reported the highest prevalence of anemia in the country, exceeding 70% in infants and young children. Objective To assess the impact of the new WHO cutoffs on anemia prevalence and evaluate whether they affected the proportion of anemia attributable to iron deficiency (ID), inflammation, and other causes. Methods A cross-sectional study was conducted among 310 children aged 6–59 months in Puno, Peru. Participants were recruited via convenience sampling during routine medical check-ups. Venous blood samples were analyzed using an automated hemoglobin analyzer and serum biomarker evaluations. Anemia prevalence was determined based on WHO guidelines for children aged 6−59 months (and 6−23 months and 24−59 months as subgroups). The ratio of anemia due to ID (Ferritin <12 ng/mL) or inflammation (IL-6 > 60 pg/mL) was estimated using adjusted Poisson regression models, reporting prevalence ratios (PR). Results Applying the new WHO guidelines, anemia prevalence changed from 50% to 42.2% in children aged 6−59 months (62% to 47% in children aged 6−23 months and from 45.9% to 40.6% in children aged 24−59 months). The proportion of anemia due to ID was 27.5%, due to inflammation was 45.9%, and due to other causes was 26.6%. ID was significantly associated with anemia in both unadjusted and adjusted analyses (PR: 1.4, 95% CI: 1.1–1.8; PR: 1.32, 95% CI: 1.0–1.7). The 2024 WHO guidelines did not substantially alter the estimated proportion of anemia associated with ID or inflammation. Conclusions Application of the new WHO cutoffs resulted in a lower estimated prevalence of anemia among young children. ID accounted for only a small proportion of cases of anemia, emphasizing the need for further research into other causes of childhood anemia in Peru.